Gestion De L’espace Scolaire Dans Les Lycées Publics d’Abidjan : La Contribution De l’Education Relative À l’Environnement - Koffi, Affoué Philomène; Julie, N’chot Apo; Kouadio, M’bra Kouakou Dieu-donné (European Scientific Journal, ESJ, 2017)
Environmental Education (ERE) in Ivorian schools aims at teaching reflexes eco-citizens to learners. However, the observation of school space indicates that these eco-actions are not always applied. The objective of this study is to analyze the contribution of the ERE to the management of high schools in Abidjan. The comparative method mobilized for this purpose integrates qualitative and quantitative approaches through individual and group interviews as well as questionnaires. 169 people in safe institutions and 173 in unsafe facilities participated in the study. The results indicate that the quality of the ERE influences the sense of belonging of the actors and directs their management of the school space. In healthy establishments, the teachings are both theoretical and practical, which facilitates their application through the maintenance and preservation of the environment. On the other hand, in unsafe establishments, apart from formal activities, few initiatives relating to respect for the environment are observed. The absence of the resulting sense of belonging explains why learners perceive activities related to environmental maintenance as chores and deteriorate educational facilities. Ultimately, the ERE makes it possible to give an environmental consciousness to the learners, hence the need for its institutionalization.